Characterizing the Role of Orco Gene in Detecting Aggregation Pheromone and Food Resources in Protaetia brevitarsis Leiws (Coleoptera: Scarabaeidae) - Zhang, Xiaofang; Liu, Panjing; Qin, Qiuju; Li, Min; Meng, Runjie; Zhang, Tao (Frontiers in Physiology, 2021)
An accurate olfactory system for recognizing semiochemicals and environmental chemical signals plays crucial roles in survival and reproduction of insects. Among all olfaction-related proteins, olfactory receptors (ORs) contribute to the conversion of chemical stimuli to electric signals and thereby are vital in odorant recognition. Olfactory receptor co-receptor (Orco), one of the most conserved ORs, is extremely essential in recognizing odorants through forming a ligand-gated ion channel complex with conventional ligand-binding odorant receptors. We have previously identified aggregation pheromone in Protaetia brevitarsis (Coleoptera: Scarabaeidae), a native agricultural and horticultural pest in East-Asia. However, to our best knowledge, its olfaction recognition mechanisms are still veiled. To illustrate how P. brevitarsis recognize aggregation pheromone and host plants, in the present study we cloned and sequenced the full-length Orco gene from P. brevitarsis antennae (named PbreOrco) and found that PbreOrco is highly conserved and similar to Orcos from other Coleoptera insects. Our real-time quantitative PCR (qRT-PCR) results showed that PbreOrco is mainly expressed in antenna. We also demonstrated that silencing PbreOrco using RNA interfering through injecting dsOrco fragment significantly inhibited PbreOrco expression in comparison with injecting control dsGFP and subsequently revealed using electroantennogram and behavioral bioassays that decreasing PbreOrco transcript abundance significantly impaired the responses of P. brevitarsis to intraspecific aggregation pheromone and prolonged the time of P. brevitarsis spending on food seeking. Overall, our results demonstrated that PbreOrco is crucial in mediating odorant perception in P. brevitarsis.